Development and in vitro evaluation of oral dissolvable films of diclofenac sodium using albizia and khaya gums as film forming polymers - Bonsu, Martina Aduenimaa (2016)
A thesis submitted to the School of Graduate Studies in partial fulfilment of the requirements for the degree of Master of Philosophy (pharmaceutics), 2015